'There are no other options for us because of who we are': employment and retention in care among gay and bisexual men and transgender women living with HIV in Guatemala. Issue 5 (4th May 2021) - Munson, Alexandra J.; Davis, Dirk A.; Barrington, Clare
Abstract: The purpose of this study was to improve understanding of the relationship between employment and retention in HIV care among gay and bisexual men and transgender women in Guatemala. We interviewed gay and bisexual men ( n  = 18) and transgender women ( n  = 9) receiving care at HIV clinics in three Guatemalan cities. Thematic coding and narrative analysis were used to describe employment experiences and identify employment factors that enabled or hindered retention within the broader context of participants' lives. Employment types ranged from formal, salaried positions to informal jobs; several participants were unemployed. Intersecting stigma related to HIV status, sexual orientation and gender identity reduced participants' ability to find and maintain stable, adequately compensated work. Job opportunities were particularly limited for transgender women due to discrimination related to gender identity. Among gay and bisexual men, discrimination related to HIV was the most salient barrier to employment. Three main employment-related determinants of retention were identified: work schedule, relationships with employers, and income. HIV care and treatment services should be strategically located and have flexible hours tailored to the employment schedules and needs of key populations living with HIV. Social protection programmes are needed to foster quality employment opportunities that facilitate attendance at HIV care appointments.